Basic Concept of Cell: A Narrative Review - Hidayat, Rachmat; Joko Marwoto; Lusia Hayati (HM Publisher, 2021)
All body functions depend on cell integrity. Therefore, understanding cell biology is intrinsically important for understanding disease. A vast amount of information reveals how the cell behaves like an organism with many social cells. At the heart of cell biology is cell communication—how messages originate and are transmitted, received, interpreted, and used by cells. This efficient communication between, and within the cell maintains the function of the cell and its specialization. Intercellular signals enable each cell to determine its position and specific role. Cells must demonstrate a